2020
DOI: 10.1101/2020.10.08.331025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dementia risk factors modify hubs but leave other connectivity measures unchanged in asymptomatic individuals: a graph theoretical analysis

Abstract: BackgroundAlzheimer’s Disease (AD) is the most common form of dementia with genetic and environmental risk contributing to its development. Graph theoretical analyses of brain networks constructed from structural and functional MRI measurements have identified connectivity changes in AD and individuals with mild cognitive impairment (MCI). However, brain connectivity in asymptomatic individuals at risk of AD remains poorly understood.MethodsWe acquired diffusion-weighted magnetic resonance imaging (dMRI) data … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We recently explored the repeatability of structural brain graphs, their edge weights and graph‐theoretical metrics, for 21 different edge‐weighting schemes (Messaritaki, Dimitriadis, & Jones, 2019a ). We demonstrated that integrating several metrics as edge weights is very good at capturing differences between populations, and is interesting from the perspective of developing biomarkers (Clarke, Messaritaki, Dimitriadis, & Metzler‐Baddeley, 2021 ; Dimitriadis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…We recently explored the repeatability of structural brain graphs, their edge weights and graph‐theoretical metrics, for 21 different edge‐weighting schemes (Messaritaki, Dimitriadis, & Jones, 2019a ). We demonstrated that integrating several metrics as edge weights is very good at capturing differences between populations, and is interesting from the perspective of developing biomarkers (Clarke, Messaritaki, Dimitriadis, & Metzler‐Baddeley, 2021 ; Dimitriadis et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…It is noteworthy that the correlations were highest for the delta band, regardless of the pair of algorithm/metric used. We note that the composite structural connectomes that were derived with the algorithm of Dimitriadis et al (2017) , even though very good at capturing differences between populations ( Clarke, Messaritaki, Dimitriadis, & Metzler-Baddeley, 2020 ; Dimitriadis et al, 2017 ), did not provide any improvement in the relationship between structure and function compared to the single-metric structural connectomes, possibly because the true relationship is more complex than that implied by the linear data-driven algorithm. For that reason we do not discuss them any further.…”
Section: Resultsmentioning
confidence: 87%
“…APOE4 status also affects the clustering coefficient and the local efficiency of structural brain networks (Ma et al, 2017). Middle-aged adults with genetic, family and lifestyle risks of developing AD have a hub in their structural connectome that is not present in the structural connectome of people with no such risks of developing AD (Clarke et al, 2020). Significant functional connectivity differences in the brain networks implicated in cognition were seen in middle-aged individuals with a genetic risk for AD (Goveas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Ma et al (2017) observed that the values for the APOE4 carriers were higher than those of the non-carriers in a normal-cognition group, while the opposite pattern was observed in a group of participants suffering from Mild Cognitive Impairment (MCI). Middle-aged adults with genetic, family and lifestyle risks of developing AD have a hub in their structural connectome that is not present in the structural connectome of people with no such risks of developing AD (Clarke et al, 2020). Significant functional connectivity differences in the brain networks implicated in cognition were seen in middle-aged individuals with a genetic risk for AD (Goveas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%